KERJASAMA PT. PAL INDONESIA DAN DEPARTMENT OF NATIONAL DEFENCE (DND) FILIPINA DALAM MENINGKATKAN INDUSTRI PERTAHANAN MARITIM - Hastadilan, M. Pahlan; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research describes the cooperation between Indonesia and the Philippines in improving the maritime industry. International economic cooperation is aimed at providing benefits to each country. International cooperation is a cooperative relationship between two or more countries to achieve certain goals. PT PAL is the largest maritime manufacturing company in Indonesia, has business advantages in the design and build capabilities of warships, commercial vessels and general engineering (General Eingineering). The capability and capacity of PT PAL Indonesia as a national shipping industry shows positive movements in the economic sector, This research was carried out descriptive qualitative using library research as a method of collecting data from books, journals, websites and related documents. This research uses an international collaborative research framework. The results of this paper explain that the export of Landing Platform Dock (LPD) warships to the Philippines has had an impact on cooperation between the two countries. Where currently Indonesia is considered a strategic partner by the Philippines in terms of maritime defense development. Then it also has an impact on the national maritime defense industry, where currently PT. PAL Indonesia has been tested and recognized internationally as a company capable of producing equipment or weapons related to maritime defense. Then the export of the Landing Platform Dock (LPD) warship to the Philippines also became one of the embodiments of Indonesia's vision as the world's maritime axis. Keywords: Strategy, Cooperations, Maritm, PT,PAl, Department of National Defense, Filipina, Landing Platform Dock.